Perceptions of Police Practice, Cynicism of Police Performance, and Persistent Neighborhood Violence: An Intersecting Relationship. Issue 1 (January 2015) - Corsaro, Nicholas; Frank, James; Ozer, Murat
Abstract Purpose A growing literature indicates that legal cynicism at the neighborhood level corresponds with retaliatory homicides and persistent homicide rates, net of controls. However, no study to date has examined: a) how cynicism of police performance might be influenced by specific experiences with and perceptions of the police, and b) whether neighborhood cynicism of police performance is associated with violent crime beyond homicides. Method This study analyzed citizen and neighborhood data from Cincinnati, Ohio in the late 1990s - a social setting that had antagonistic police-community relationships. Results The results revealed that perceived unjust policing was the strongest individual level correlate of cynicism of police services, and that aggregate levels of cynicism predicted both homicides and overall violence above and beyond social disorganization as well as previous levels of violence. Conclusion We speak to the importance of these findings in terms of identifying which police-community factors seemingly have the greatest likelihood to facilitate the association between cynicism and persistent neighborhood violence.